Sustained decrease in gastroenteritis-related deaths and hospitalizations in children less than 5 years of age after the introduction of rotavirus vaccination: a time–trend analysis in Brazil (2001–2010) - Costa, Iolanda (2016)
Background: Rotavirus (RV) vaccine, Rotarix, was introduced into the Brazil national immunization program in 2006. To estimate populationlevel vaccine effect, we conducted a time–trend analysis on all-cause gastroenteritis (GE)-related death certificate–reported deaths (DCRDs), hospital deaths (HDs) and hospitalizations trends in <5-year-olds before and after RV vaccine introduction. Methods: National level all-cause GE-related death certificate [Mortality Information System] and admission (Hospital Information System) data were aggregated and analyzed. Negative-binomial regression models (adjusting for age, year and region) compared DCRDs, HDs and hospitalization trends in <5-year-olds between baseline (2001−2005) and postvaccine introduction periods (Mortality Information System: 2007−2009 and Hospital Information System: 2007−2010). Negative-binomial regression models were fitted to data for each outcome before 2006, and the predicted annual frequencies of each outcome were plotted against corresponding observed annual frequencies. Results: During the postvaccine introduction period, there was an overall age-independent GE-related DCRDs reduction (20.9%, P = 0.04) observed in children <5 years of age; a reduction was also seen in infants <1 year of age (20.8%, P = 0.003). Age-independent GE-related HDs and hospitalizations reductions (57.1%, P < 0.0001 and 26.6%, P < 0.0001, respectively) were observed in <5-year-olds; HDs reductions were also observed for each age group (<1-year-olds: 55.0%, P < 0.0001 and 1- to <5-year-olds: 59.5%, P < 0.0001). Observed annual frequencies of GE-related DCRDs, HDs and hospitalizations were lower than the predicted value in each age group in all years after 2006. Conclusions: GE-related DCRDs, HDs and hospitalizations were significantly reduced in <1 and in 1- to <5-year-old Brazilian children after Rotarix introduction, which provides additional evidence of the direct and indirect population-level effect of RV vaccination on GE-related mortality and morbidity in children.